Specificity of the operator’s activity performing the work with the forecasting tools of technologically and chronologically interconnected events in the system of continuous forecasting and tracking information flows - V. V. Savluchinskij (Системный анализ и прикладная информатика)
Creation of an automated continuous forecasting system based on tracking information flows requires the development of a number of algorithms and machine programs to build a model of the forecast object based on the obtained identification features, to optimize a branched technologically and chronologically interconnected network of hierarchically coordinated events with an example of the work of the operator performing the work with the prediction tool in the system continuous forecasting and tracking information E flows.